Emotional interference-based forgetting in short-term memory. Cognitive inhibition of pleasant but not unpleasant biologically relevant distractors - García-Pacios, Javier; Del Río, David; Villalobos, Dolores; Ruiz-Vargas, José M.; Maestú, Fernando (Frontiers in Psychology, 2015)
Emotional stimuli automatically recruit attentional resources. Although this usually brings more adaptive responses, it may suppose a disadvantage when emotional information is task-irrelevant and should be ignored. Previous studies have shown how emotional stimuli with a negative content exert a greater interference than neutral stimuli during a concurrent working memory (WM) task. However, the impact of positively valenced stimuli as interference has not been addressed to date. In four experiments we explore the impact of pleasant and unpleasant emotional distractors during WM maintenance. The results suggest that our cognitive control can cope with the interference posed by pleasant distractors as well with the interference posed by neutral stimuli. However, unpleasant distractors are harder to control in the context of WM maintenance. As unpleasant stimuli usually convey relevant information that we should not to ignore, our executive control seems to be less able to reallocate cognitive resources after unpleasant distraction.